Faktor Kecenderungan Keluarga Dalam Mengungkapkan Alasan Penyalahgunaan NAZA: Sebuah Konteks Komunikasi Antarpribadi - Nurlina Rahman (Jurnal Inovasi Pendidikan Dasar, 2017)
The aim of this research is to find the reason for the user of subtance abuse by understanding family factor as one of tendency factors. Research method was a qualitative phenomology. The research subject was 16 people that majority were age of 10 – 16 years old when started using drugs (1 person started using drugs in primary school). Sampling techniques were quota sampling and snow-ball sampling. The result showed that someone will be involved in subtance abuse until addicted phase if there was a tendency factor. The tendency factor was family factor that can be a trigger of subtance abuse. Therefore, this research was expected to give understanding in society especially family and educational authority to aware the early symptoms of subtance abuse. This case has been a concern of social phenomenon because drug trafficking has entered the age of primary school.